RELASI-RELASI KEKUASAAN DI BALIK PEN'GELOLAAN INDUSTRI PARIWISATA BALI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Knowledge hidden in the discourse of tourism in the official speech of President Soeharto August 16, 1968 made by the local government authority by issuing an expression Bali discourse of Cultural Tourism. However, tourism is initially expected to be one source of foreign exchange, was stagnated in 1976 and lasted for a decade. It gives an opportunity for conservative organic intellectuals ff"omvarious schools to achieve the interests of each group. That is why behind the management of the tourism industry hidden relations of power. Hidden phenomenon is described in this study using a ff"ame of mind Michel Foucault on Power and Knowledge. The use of a ff"ame of mind that facilitates the application of historical methods is ranging from heuristic to synthesis. Through the workings of it, it can be seen almost all of the organic intellectual conservative who has managed to capture the knowledge of the power speak hidden behind the phrase discourse of Cultural Tourism for the benefit of each group. Keywords: cultural tourism, PKB, Ekadasarudra, invented art, organic intellectuals